Geografia polityczna województwa lubuskiego po wyborach roku 2006: analiza wybranych zagadnień = Political geography of the Lubuskie province after the 2006 elections: analysis of selected issues - Flakowski, Jarosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents selected problems concerning the local elections which took place in 2006 in the Lubuskie province. The inhabitants of this region chose 1563 of 9647 legal candidates and 83 representatives for executive organs in the commune.
Keywords: województwo lubuskie; wybory samorządowe; historia; od 1989 r.